Bipolar membrane electrode assemblies for water electrolysis - Thiele, Simon; Mayerhöfer, Britta; McLaughlin, David; Böhm, Thomas; Hegelheimer, Manuel; Seeberger, Dominik (ACS Applied Energy Materials, 2020)
We present the first analysis of a zero-gap bipolar membrane water electrolyzer fed with liquid water. Our electrolyzers feature a high-pH environment for the oxygen evolution reaction and a low-pH environment for the hydrogen evolution reaction. The advantages of proton exchange membrane water electrolysis can be combined with those of anion exchange membrane water electrolysis by including a water splitting bipolar interface. First, we develop a KOH-free anion exchange membrane electrolysis cell. The cell's alkaline anode serves as an integral building block on the path to a bipolar system. In a second step, we use this building block to investigate the cell operation characteristics of various cell configurations. We study the cell performance as the bipolar interface is shifted progressively toward the anode. A bipolar membrane with and without a water splitting catalyst resulted in cell current densities of 450 and 5 mA cm−2 at cell voltages of 2.2 V, respectively. Upon moving the bipolar interface directly between the acidic membrane and the high-pH anode, we achieved current densities of 9000 mA cm−2 at cell voltages of 2.2 V. Our study demonstrates the potential of this water electrolysis configuration, which should be adopted for further scientific studies and may show promise for future commercial water electrolysis systems.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Additive manufacturing; Aemion; Anion exchange membrane; Bipolar membrane; PH gradient; Water electrolysis; Water splitting

Directly coated membrane electrode assemblies for proton exchange membrane water electrolysis - Holzapfel, Peter; Bühler, Melanie; Van Pham, Chuyen; Hegge, Friedemann; Böhm, Thomas; McLaughlin, David; Breitwieser, Matthias; Thiele, Simon (Electrochemistry Communications, 2020)
We present a novel membrane electrode assembly (MEA) fabrication method for proton exchange membrane water electrolysis (PEMWE). Inspired by previous work on PEM fuel cells (PEMFCs), we fabricated PEMWE-MEAs via direct membrane deposition (DMD). DMD-MEAs were fabricated by spray coating the membrane directly onto the cathode electrode – in this case, a carbon cloth substrate with microporous layer coated with Pt/C. The complete DMD-MEAs consisted of the membrane-cathode compound assembled with an anode electrode, which is a porous titanium fiber substrate coated with IrO2. Polarization experiments of DMD-MEAs show promising results: In comparison to a reference catalyst coated membrane (CCM) and a porous transport electrode (PTE) type MEA using a freestanding Nafion 117 membrane, we found very good electrochemical performances for DMD-MEAs. DMD-MEAs show slightly higher activation losses than the reference CCM. However, DMD-MEAs seem to exhibit reduced ohmic and mass transport losses compared to those manufactured using the CCM approach. Compared to the PTE-type reference DMD shows improvements for all three loss mechanisms. Similar as for PEMFCs, DMD may allow for a simplified fabrication route and higher degree of design freedom in PEMWE-MEA manufacturing due to the simple layer by layer fabrication approach.
CRIS-Team Scopus Importer:2019-12-27
Keywords: Direct membrane deposition; PEM water electrolysis; Porous transport electrodes

Improved Hydrogen Oxidation Reaction Activity and Stability of Buried Metal-Oxide Electrocatalyst Interfaces - Speck, Florian D.; Ali, Farhan S. M.; Paul, Michael T. Y.; Singh, Ramesh K.; Böhm, Thomas; Hofer, André; Kasian, Olga; Thiele, Simon; Bachmann, Julien; Dekel, Dario R.; Kallio, Tanja; Cherevko, Serhiy (Chemistry of Materials, 2020)
Various bifunctional metal-oxide composites have recently been proposed as advanced hydrogen oxidation reaction (HOR) electrocatalysts for anion-exchange membrane fuel cells (AEMFCs). It is postulated that metal and oxide are active sites for the adsorption of hydrogen/proton and hydroxide ions, respectively. Of particular interest are the so-called buried interfaces. To investigate processes governing activity and stability at such interfaces, we prepare model Pd and Pt electrocatalysts which are fully covered by thin CeOx films. We investigate how oxide thickness influences HOR activity and dissolution stability of the electrocatalysts. It is found that materials behave very differently and that only Pd exhibits an enhanced HOR activity, while both oxide-protected metals are more stable toward dissolution. A 10-fold decrease in dissolution and 15-fold increase in HOR exchange current density are demonstrated for the optimized Pd/CeOx composites in comparison to pure Pd. We assess the mechanism of the electrocatalytic improvement as well as the role of the protective oxide films in such systems through advanced electrochemical and physical analysis. It is highlighted that a uniform, semipermeable oxide layer with a maximized electrocatalyst-oxide interface is crucial to form HOR catalysts with improved activity and stability.
CRIS-Team WoS Importer:2020-10-23

On the limitations in assessing stability of oxygen evolution catalysts using aqueous model electrochemical cells - Knöppel, Julius; Möckl, Maximilian; Escalera-López, Daniel; Stojanovski, Kevin; Bierling, Markus; Böhm, Thomas; Thiele, Simon; Rzepka, Matthias; Cherevko, Serhiy (Nature Communications, 2021)
Recent research indicates a severe discrepancy between oxygen evolution reaction catalysts dissolution in aqueous model systems and membrane electrode assemblies. This questions the relevance of the widespread aqueous testing for real world application. In this study, we aim to determine the processes responsible for the dissolution discrepancy. Experimental parameters known to diverge in both systems are individually tested for their influence on dissolution of an Ir-based catalyst. Ir dissolution is studied in an aqueous model system, a scanning flow cell coupled to an inductively coupled plasma mass spectrometer. Real dissolution rates of the Ir OER catalyst in membrane electrode assemblies are measured with a specifically developed, dedicated setup. Overestimated acidity in the anode catalyst layer and stabilization over time in real devices are proposed as main contributors to the dissolution discrepancy. The results shown here lead to clear guidelines for anode electrocatalyst testing parameters to resemble realistic electrolyzer operating conditions.
CRIS-Team Scopus Importer:2021-04-30

Platinum Dissolution in Realistic Fuel Cell Catalyst Layers - Ehelebe, Konrad; Knöppel, Julius; Bierling, Markus; Mayerhöfer, Britta; Böhm, Thomas; Kulyk, Nadiia; Thiele, Simon; Mayrhofer, Karl; Cherevko, Serhiy (Angewandte Chemie International Edition, 2021)
Pt dissolution has already been intensively studied in aqueous model systems and many mechanistic insights have been gained. Nevertheless, transfer of new knowledge to real-world fuel cell systems is still a significant challenge. To close this gap, we present a novel in situ method combining a gas diffusion electrode (GDE) half-cell with inductively coupled plasma mass spectrometry (ICP-MS). With this setup, Pt dissolution in realistic catalyst layers and the transport of dissolved Pt species through Nafion membranes were evaluated directly. We observed that 1) specific Pt dissolution increased significantly with decreasing Pt loading, 2) in comparison to experiments on aqueous model systems with flow cells, the measured dissolution in GDE experiments was considerably lower, and 3) by adding a membrane onto the catalyst layer, Pt dissolution was reduced even further. All these phenomena are attributed to the varying mass transport conditions of dissolved Pt species, influencing re-deposition and equilibrium potential.
CRIS-Team WoS Importer:2021-03-12

Serial section Raman tomography with 10 times higher depth resolution than confocal Raman microscopy - Böhm, Thomas; Moroni, Riko; Thiele, Simon (Journal of Raman Spectroscopy, 2020)
Confocal Raman microscopy enables 3D imaging of various samples solely based on chemical contrast. However, optical artifacts impair resolution and image quality in subsurface imaging. With serial section Raman tomography, we show that serial ultrathin and semithin sectioning by ultramicrotomy can successfully be combined with subsequent confocal Raman imaging. This new 3D Raman imaging technique reaches a depth resolution of up to 100 nm, which is about 10-fold better than in confocal Raman microscopy. Structurally complex and optically inhomogeneous samples can not only be imaged, but also be used to quantify structural parameters. Serial section Raman tomography is a promising method for materials science and possibly also for life sciences.
CRIS-Team Scopus Importer:2020-03-31
Keywords: 3D reconstruction; polymer; Raman imaging; serial sectioning; tomography

Spatially and temporally resolved monitoring of doping polybenzimidazole membranes with phosphoric acid - Arslan, Funda; Böhm, Thomas; Kerres, Jochen; Thiele, Simon (Journal of Membrane Science, 2021)
Polybenzimidazole-based membranes in high temperature proton exchange membrane fuel cells require doping with phosphoric acid to enable proton conductivity. The level of phosphoric acid doping is traditionally determined by titration or weighing, but these methods only provide limited information, since they do not offer spatial resolution. We show that confocal Raman microscopy can not only provide information on the level of doping, but in addition about the spatial distribution of the dopant. We prove that doping is a diffusion-limited process, leading to a spatially inhomogeneous distribution of phosphoric acid unless doping is performed to saturation. Further, evidence of a slow redistribution of the dopant within a freestanding membrane under ambient conditions is provided. Confocal Raman microscopy can be used as a non-invasive measurement tool to investigate status and progress of doping a membrane with phosphoric acid.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Acid doping level (ADL); Acid uptake (AU); Fuel cells (FCs); High temperature (HT); Phosphoric acid (PA); Polybenzimidazole (PBI); Polymer electrolyte membrane; Raman spectroscopy

The kinase domain of CK1δ can be phosphorylated by Chk1 - Böhm, Thomas; Meng, Zhigang; Haas, Philipp; Henne-Bruns, Doris; Rachidi, Najma; Knippschild, Uwe; Bischof, Joachim (Bioscience Biotechnology and Biochemistry, 2019)
Members of the casein kinase 1 (CK1) family are key regulators in numerous cellular signal transduction pathways and in order to prevent the development of certain diseases, CK1 kinase activity needs to be tightly regulated. Modulation of kinase activity by site-specific phosphorylation within the C-terminal regulatory domain of CK1δ has already been shown for several cellular kinases. By using biochemical methods, we now identified residues T161, T174, T176, and S181 within the kinase domain of CK1δ as target sites for checkpoint kinase 1 (Chk1). At least residues T176 and S181 show full conservation among CK1δ orthologues from different eukaryotic species. Enzyme kinetic analysis furthermore led to the hypothesis that site-specific phosphorylation within the kinase domain finally contributes to fine-tuning of CK1δ kinase activity. These data provide a basis for the extension of our knowledge about the role of site-specific phosphorylation for regulation of CK1δ and associated signal transduction pathways.
CRIS-Team Scopus Importer:2019-08-23
Keywords: Casein kinase 1; Checkpoint kinase 1; Enzyme kinetics; Phosphopeptide analysis; Site-specific phosphorylation